2016
DOI: 10.1016/j.biocel.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Personalized liposome–protein corona in the blood of breast, gastric and pancreatic cancer patients

Abstract: When nanoparticles (NPs) are dispersed in a biofluid, they are covered by a protein corona the composition of which strongly depends on the protein source. Recent studies demonstrated that the type of disease has a crucial role in the protein composition of the NP corona with relevant implications on personalized medicine. Proteomic variations frequently occur in cancer with the consequence that the bio-identity of NPs in the blood of cancer patients may differ from that acquired after administration to health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 42 publications
4
90
0
Order By: Relevance
“…The results of the first study were confirmed by Colapicchioni et al 26 (Figure 3) in the course of evaluating PPCs formed on clinically approved liposomes (AmBisome) in gastric, breast, and pancreatic cancer patients (10 individuals per disease). The authors found that changes in the liposome’s size attributable to the PC were similar between healthy volunteers and cancer patients.…”
Section: Disease-induced Variability In the Protein Corona Compositionsupporting
confidence: 55%
See 2 more Smart Citations
“…The results of the first study were confirmed by Colapicchioni et al 26 (Figure 3) in the course of evaluating PPCs formed on clinically approved liposomes (AmBisome) in gastric, breast, and pancreatic cancer patients (10 individuals per disease). The authors found that changes in the liposome’s size attributable to the PC were similar between healthy volunteers and cancer patients.…”
Section: Disease-induced Variability In the Protein Corona Compositionsupporting
confidence: 55%
“…Herein we introduce two recent studies featuring extensive analysis of changes in the PC composition in a wide range of diseases. 20,26 …”
Section: Disease-induced Variability In the Protein Corona Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…2022, 183 Therefore, this “disease-specific” protein corona adds complications to the actual in vivo intracellular trafficking of NPs and needs more attention in future studies.…”
Section: Intracellular Traffickingmentioning
confidence: 99%
“…[219] Since many diseases affect both the concentration and the composition of plasma proteins, any drug carrier administered to patients will be exposed to biological environments that vary depending on the disease. [219,220] Furthermore, even patients with the same type of disease can show variations in the concentration and composition of plasma proteins, due to differences in age, gender, medical history etc. [221] Therefore, for drug carriers administered to patients, different biomolecular coronas will form.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%